VALIDATION OF ULTRAVIOLET SPECTROPHOTOMETRY METHOD FOR DETERMINATION OF MEFENAMIC ACID LEVEL IN SUSPENSION DOSAGE FORMS - Nerdy Nerdy (Jurnal Natural, 2017)
Abstract. Mefenamic Acid is one type of nonsteroidal antiinflammatory drug that works to relieve pain by blocking an enzyme that produces prostaglandins. The quality requirements that must be met by pharmaceutical preparations are levels contained must meet the level requirement as listed in the Indonesian Pharmacopoeia or other standard books. The purpose of this study was to conduct a validation test of ultraviolet spectrophotometry methods for determination of the Mefenamic Acid level in the suspension preparation. The sample consisted of three suspensions preparation under the trade name obtained from a pharmacy in the Medan city. The solvent used is sodium hydroxide (NaOH) 0,1 N solution and the measurement was done at a wavelength of 286 nm. Validation parameters determined were Accuracy, Precision, Linearity, Range, Limit of Detection and Limit of Quantitation. The results of the determination of the Mefenamic Acid suspension preparation under the trade name Pondex® was 100,39±0,21%, trade name Omestan® was 99,98±0,33% and trade name Novastan® was 103,21±0,83%. All the suspension preparations were determined meet the general level requirement, that contain not less than 90,0% and not more than 110,0% of the amount stated on the label. The results meet the requirements of the validation test of analysis methods with the parameter percent recovery 100,08% for accuracy, relative standard deviation 0,04% for precision, the correlation coefficient 1,0000 for linearity, range 8 μg/mL to 12 μg/mL, limit of detection limit 0,0118 μg/mL, limit of quantitation 0,0356 μg/mL. Keywords: Validation, Spectrophotometry, Determination, Suspension, Mefenamic Acid